Determinants of coinfection tuberculosis and HIV in prisons in Brazil - Nanci Michele Saita; Rubia Laine de Paula Andrade; Pedro Augusto Bossonário; Rafaele Oliveira Bonfim; Jordana de Almeida Nogueira; Antônio Ruffino Netto; Ricardo Alexandre Arcêncio; Tereza Cristina Scatena Villa; Aline Aparecida Monroe (Journal of Infection in Developing Countries)
Introduction: Prisons context has the potential for the spread of infectious diseases, like HIV and tuberculosis, which prevalence is higher in the people deprived of liberty compared to the general population.